La Inclusión en el Ambiente de Aprendizaje de los niños de 4 a 5 años del Centro de Educación Inicial “GAIA”, Ciudad de Riobamba - Bazurto Solorzano, Kenvy Domenica (2023)
The present work entitled inclusion in the learning environment, which has the meaning of adding, summing or including someone in a group of which they were not a part before, to work with equal rights and opportunities to fulfill themselves as individuals. Its main objective is to express the importance of inclusion in the learning environment, for which the research methodology of a bibliographic support was applied to take information from different websites such as: books, articles, thesis, journals, among others. Its design is nonexperimental so that situations that already exist within the educational establishment were observed, field because it was carried out in the "Gaia" initial education center, with 4 to 5 years old students, who belong to the initial level. 2, observation was used as the main technique and a form was used as an instrument, applied to the children and teachers. Among the achievements of this study, it can be said that the management of the learning environment elements and the application of different activities result in good academic performance and safe inclusion for all, to benefit the entire institutional population.